Perancangan Blind Stick Berbasis ESP32 dengan Sensor Ultrasonik untuk Membantu Mobilitas Penyandang Tunanetra - Latief Naufal Andryanto; Azmi Nur Shidiq Ridzwan; Rachel Disa Talitha Rachma; Acep Tio; Muhammad Syahran Mawarid Taslim; Nabil Muflih Wardana (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Mobility is one of the major challenges for visually impaired individuals in their daily activities. Visual impairments make it difficult for them to detect obstacles around them, increasing the risk of injury. This study aims to design and develop a smart stick based on ESP32, equipped with an ultrasonic sensor, to assist the mobility of visually impaired people. The system uses ultrasonic sensors to detect the distance of objects and provides early warnings to users through a buzzer, with varying rhythms depending on the proximity of objects. The research methodology includes system design and development of hardware and software, as well as direct testing on visually impaired users. The test results show that the system can detect obstacles with 95% accuracy at distances up to 200 cm, and provide appropriate responses based on the distance of detected objects. In addition, this prototype is energy-efficient, allowing for prolonged use without frequent recharging. This study provides a practical solution to enhance the independence and safety of visually impaired individuals in daily activities, with the potential for further development to improve detection accuracy and user comfort.